The genus Pereionotus (Crustacea, Amphipoda, Phliantidae) from Australia - Coleman, Ch. Oliver; Lowry, James K. (Zootaxa, 2012)
Pereionotus species from around Australia are described. The new taxa Pereionotus dieteri sp. nov. and Pereionotushartmuti sp. nov. are fully described and compared with the redescribed Pereionotus thomsoni. Species misidentified inthe past are synonymised and as a result the new taxon Pereionotus yongensis sp. nov. is introduced. A new name,Pereionotus hirayamai sp. nov., is proposed for Pereionotus thomsoni japonicus (Hirayama, 1987) (homonym of P. japonicus (Tzvetkova, 1967)). A key to the Australian species of the genus Pereionotus is given.